Transverse damage in glass fiber reinforced polymer under thermo-mechanical loading - Kraus, David; Trappe, Volker (Composites. Part C, Open access, 2021)
In this study, the thermomechanical damage behavior of a glass fiber reinforced polymer material is investigated. The coefficients of thermal expansion of the composite as well as the matrix are measured in a wide temperature range. Quasi-static experiments with neat resin, unidirectional and multidirectional laminates are performed as well as fatigue experiments in a temperature range from 213 K to 343 K. This study focusses on the matrix damage due to fiber-parallel loading. A correlation between matrix effort, the dilatational strain energy of the matrix and the damage state of the specimen is demonstrated. It is shown that a fatigue life assessment can be performed with the aid of a temperature-independent master fatigue curve.